Rantai Pasok Brokoli di Kecamatan Lembang Kabupaten Bandung Barat dengan Pendekatan Food Supply Chain Networks - Clara Yolandika; Rita Nurmalina; Suharno Suharno (Politeknik Negeri Lampung., 2016)
This study aims to determine the condition of the supply chain broccoli in the district ofBandung Lembang district west to approach food supply chain networks ( FSCN ). Thisresearch will be carried out in the CV . Yan's Fruits and Vegetable in Lembang district ,West Bandung regency, West Java. This study requires an approach to qualitative andquantitative methods for treating primary and secondary data . To analyze the supply chainqualitative and quantitative data required by the framework of the Food Supply ChainNetworking (FSCN) of Lambert and Cooper (2000) as modified by Vorst (2006).Results from this study is the condition of supply chain broccoli in Lembang district WestBandung regency based approach is the Food Supply Chain Networks as seen from thetarget supply chain, the structure of the supply chain, the entity supply chain, supply chainmanagement, resource supply chain, and business processes of supply chain is alreadyintegrated well.Keywords: Broccoli, FSCN, Supply Chain